(De)stabilization of Alpha-Synuclein Fibrillary Aggregation by Charged and Uncharged Surfactants - Joana Angélica Loureiro (MDPI AG, 2021)
Parkinson’s disease (PD) is the second most common neurodegenerative disorder. An important hallmark of PD involves the pathological aggregation of proteins in structures known as Lewy bodies. The major component of these proteinaceous inclusions is alpha (α)-synuclein. In different conditions, α-synuclein can assume conformations rich in either α-helix or β-sheets. The mechanisms of α-synuclein misfolding, aggregation, and fibrillation remain unknown, but it is thought that β-sheet conformation of α-synuclein is responsible for its associated toxic mechanisms. To gain fundamental insights into the process of α-synuclein misfolding and aggregation, the secondary structure of this protein in the presence of charged and non-charged surfactant solutions was characterized. The selected surfactants were (anionic) sodium dodecyl sulphate (SDS), (cationic) cetyltrimethylammonium chloride (CTAC), and (uncharged) octyl β-D-glucopyranoside (OG). The effect of surfactants in α-synuclein misfolding was assessed by ultra-structural analyses, in vitro aggregation assays, and secondary structure analyses. The α-synuclein aggregation in the presence of negatively charged SDS suggests that SDS-monomer complexes stimulate the aggregation process. A reduction in the electrostatic repulsion between N- and C-terminal and in the hydrophobic interactions between the NAC (non-amyloid beta component) region and the C-terminal seems to be important to undergo aggregation. Fourier transform infrared spectroscopy (FTIR) measurements show that β-sheet structures comprise the assembly of the fibrils.